Challenges of measuring the influence of the Recovery Academy upon health professionals: considerations for quantitative research. Issue 3 (22nd March 2019) - Sutton, Rebecca; French, Paul
Abstract : Purpose: The purpose of this paper is to reflect upon experiences of measuring the influences of the Recovery Academy within Greater Manchester Mental Health (GMMH) NHS Foundation Trust amongst a student population of health professionals. This paper aims to present considerations for future quantitative research surrounding the efficacy of Recovery Colleges such as the Recovery Academy. Design/methodology/approach: This paper utilised baseline data collected from health professionals as part of a quantitative evaluation of the Recovery Academy. The paper discusses challenges experienced in measuring change amongst this student population within GMMH. Findings: Health professionals reported positive attitudes towards recovery at baseline presenting challenges in measuring attitudinal change associated with the Recovery Academy. The experiences of conducting research amongst health professionals within GMMH offers insights into the selection and use of self-report measures in Recovery College research; the representativeness of health professional student populations; and models of course attendance within Recovery Colleges. Originality/value: The existing literature specific to Recovery College influences upon health professionals remains predominantly qualitative and anecdotal. It is important to gather empirical evidence regarding Recovery Colleges to establish their ability to re-orientate health professionals around principles of recovery. This paper therefore offers considerations for future researchers aiming to gather empirical evidence which may facilitate quantitative evaluations of Recovery Colleges such as the Recovery Academy amongst staff populations.